Política de comercializaç\~ao agrícola comparada: Brasil, Estados Unidos e Uni\~ao Europeia - Júnia Cristina Péres Rodrigues Da Conceiç\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
The text aimed to discuss and compare agricultural marketing policies in Brazil, the European Union and the United States, showing the changes that occurred, especially after the trade liberalization process in the 1990s. One of the main results found in the study was that Brazil provides little support to the agricultural sector, through the commercialization policy, vis-à-vis other countries and, therefore, has room for a more vigorous agricultural policy, with greater financial support to the sector. The important thing is the choice of appropriate instruments, given that budget resources are always a limiting factor. Another important point that the study highlights is that future trade agreements and changes in trade relations between participants will have strong impacts on agricultural markets and in its domestic policies to support the agricultural sector and, therefore, Brazil must be aware of the functioning of the policies of other countries.
Keywords: Q17; 330; agricultural commercialization policy; commercial agreements in agricultural areas; international trade